O BANCO MUNDIAL E A EDUCAÇÃO NO BRASIL: ESTUDO REALIZADO A PARTIR DAS TESES DEFENDIDAS NA UNIVERSIDADE ESTADUAL DE CAMPINAS (UNICAMP), NO PERÍODO DE 1995 A 2007 - Pinheiro, Patricia da Veiga (2010)
This study aims to conduct a study about the influence of the World Bank in the Brazilian educational area, from six doctoral thesis (A,B,C, D, E and F) of University of Campinas, defined during this work, which deal with issues of the World Bank in different aspects and forms. Exactly four thesis (A, B, C, and D) are comming from education area and two (E and F) in the Social Sciences and Economics area. This study begin with the objectives of each one of these thesis, which can be summarized as follows: Thesis A - "The globalization of education, the neoliberal project of Society and Education in Brazil and Venezuela" (MELO, 2003) - Doctoral dissertation in Education - Under the guidance of Nilson Joseph Demange, PhD - Presented on February 07, 2003- investigate the process of globalization of education as part of a new phase of globalization and accumulation capitalist, led by the hegemonic collective political actors who adopt neo-liberal project of social interaction, especially the International Monetary Fund and World Bank, which try to be the drivers of structural reforms for Latin America and the Caribbean; Thesis B - "The Finance Capital and Education in Brazil" (DEITOS, 2005) - Doctoral Thesis in Education - Under the guidance of Mary Elizabeth Prado Sampaio Xavier, PhD - Presented on February 28, 2005 - are set about the consequences of the consolidation project for the redefinition of educational policies in Latin America and the Caribbean; Thesis C "Globalization and Decentralization: The process of Deconstructing the Brazilian educational system by means of municipalization" ROSAR (1995) - Doctoral dissertation in Education - Under the guidance of Demerval Savian,PhD - Presented on November 24, 1995- examines educational reforms undertaken in Brazil during the period 1995-2002, particularly the national education policy for secondary education and training, with external financing from the International Bank for Reconstruction and Development (IBRD), Thesis D "Policies for Educational Development and Work of Teachers" (SOUZA, 1999) - Doctoral Thesis in Education - Under the guidance of Liliana Rolísen Petrilli Segnini, PhD - Presented on August 12, 1999 that dealing with the educational policy for teaching 1st grade, beginning in the view of its author in the context of federal projects, with the aim of inducing the decentralization of education, by transferring charge to the municipality don´t do the satisfactory investments for that instance. Thesis E "Economy, power, and external influences: The World Bank Group and the Structural Adjustment Policies in Latin America in the eighties and nineties decades" (COELHO, 2002) - PhD Thesis in Social Sciences - Under the guidance of Sebastião Carlos Velasco and Cruz, PhD - Defended on December 13, 2002 - the relationship between education project implemented by the São Paulo state government between 1995 and 1998 and their conceptions of educational policies; Thesis F "The Social Question and the Limits of the Liberal Project in Brazil" (GIMENES, 2007) Doctoral Dissertation showed to Institute of Economics Under the guidance of Carlos Alonso Barbosa de Oliveir, PhD Presented on March 08, 2007 analyze the relationship between economics, political power focusing on external influences and the World Bank Group and the structural adjustment programs in Latin America beyond the general conclusion of all theses. Finally, this study mingling brazilian thesis that cames from education and economy area, that focused World Bank influence in Brazil and offers one view of the logic conexions between them and their impacts in our society.